Performance Analysis of Modified SHA-3. (2016) - Chandran, Nithin R.; Manuel, Ebin M.
Abstract: Security services have become an inseparable feature of almost all digital transactions. A crucial module of these scheme isintegrity, which is performed using a cryptographic hash function. Secure Hash Algorithm can be an efficient hashing technique.SHA-3 is the most recent and efficient Secure Hash Algorithm. Keccak has been chosen as the official algorithm for SHA-3 in2012. In this paper we propose a modification on the design of Secure Hash Algorithm (SHA-3) on Xilinx Field ProgrammableGate Array (FPGA) device. In order to provide reliable architecture for this algorithm, a concurrent error tolerant scheme forSHA-3 is used. A system based on the combination of SHA-3 and error tolerant scheme is also described. Simulation resultsshows, an efficiency in area and delay of SHA-3 designs.